Study Of Deradicalization And Disengagement Of Former Terrorism Convicts As An Effort To Prevent Terrorism For National Resilience - Anastasia I. K (Publikasi Indonesia, 2023)
Terrorism is an issue of particular concern worldwide because of its global threat. The Indonesian government realizes that terrorism is an extraordinary event that requires special handling, hence, the appropriate countermeasure is needed. One of the ways to achieve it is by deradicalization and disengagement of former convicts in terrorism cases. This article aims to determine the role of deradicalization and disengagement methods for ex-convicts in terrorism cases as a strategy for dealing with criminal acts of terrorism in Indonesia. The research method used in this study was literature research, which was then analyzed using qualitative content analysis. Deradicalization programs require many approaches which depend on the individual’s characteristics in understanding the process of radicalization that occurs and is experienced by certain individuals or groups. So that by understanding the interpretation of the deradicalization polemic that is occurring, a new formulation is needed for the treatment of convict convicts. Effective methods of deradicalization and disengagement rehabilitation, continuous testing, periodic assessment, and strict supervision, carried out by the state in a comprehensive manner, can undoubtedly be a form of great support, specifically, for ex-convicts to not return and join their radical groups and leave violent ways.